AI-Enhanced Social Media Campaigns: Influence on Women's Empowerment and Community Engagement - Ezeakolam , Amarachi Agatha; Adelabu , Omowale Taofeek (Corpus Intellectual, 2025)
The emergence of artificial intelligence (AI) has the ability to significantly amplify the reach and impact of social media campaigns especially in areas of women's empowerment which involves improving the social, economic, political, and legal strength of women through personalise content and enhanced engagement. This study aims to: (1) examine how AI tools affect the dissemination and reception of information about women's empowerment campaigns; (2) assess the impact of AI-powered communication strategies to increase participation in women’s empowerment campaign programmes; and (3) to identify challenges that may impede the success of these campaigns such as personal bias, privacy concerns and digital divide. There are reports of women benefiting from technological advancement, yet these improvements have not adequately addressed the lots of women. The Diffusion of Innovation Theory was used to understudy this research work providing a structured approach to understanding the adoption and spread of AI technologies in social media messages on women's empowerment campaigns. This study employed conceptual analysis method to look at existing literature on AI, social media, and women's empowerment, offering a comprehensive analysis of how AI-enhanced campaigns can support the empowerment of women. Findings from existing literatures suggest that AI-enhanced social media campaigns have the potential to revolutionise communication on women's empowerment initiatives by making outreach efforts more personalised, efficient and targeting the right audience. However, the study anticipates challenges related to privacy invasion, personal bias and unequal access to digital technologies, which may affect the equitable spread of such innovations.